2012
DOI: 10.1073/pnas.1213569110
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent dopamine tracer resolves individual dopaminergic synapses and their activity in the brain

Abstract: We recently introduced fluorescent false neurotransmitters (FFNs) as optical tracers that enable the visualization of neurotransmitter release at individual presynaptic terminals. Here, we describe a pH-responsive FFN probe, FFN102, which as a polar dopamine transporter substrate selectively labels dopamine cell bodies and dendrites in ventral midbrain and dopaminergic synaptic terminals in dorsal striatum. FFN102 exhibits greater fluorescence emission in neutral than acidic environments, and thus affords a me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
142
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 107 publications
(154 citation statements)
references
References 30 publications
8
142
0
2
Order By: Relevance
“…6 C and D). Interestingly, the 10% decrease in mean fluorescence is comparable to the decrease found using similar stimulation in the striatum with the false fluorescent neurotransmitter FFN102 before separating responders from nonresponders (11). Again, removing Ca 2+ was inhibitory.…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…6 C and D). Interestingly, the 10% decrease in mean fluorescence is comparable to the decrease found using similar stimulation in the striatum with the false fluorescent neurotransmitter FFN102 before separating responders from nonresponders (11). Again, removing Ca 2+ was inhibitory.…”
Section: Resultssupporting
confidence: 54%
“…Furthermore, pCA experiments suggest that VMAT-containing organelles in the soma are sparse, and therefore obscured by other acidic organelles or are not acidified. It is also possible that 20 min of pCA treatment was too short to detect a somatic CYAM response, because the false fluorescent neurotransmitter FFN102 is released from the soma of DA neurons only after 40 min of incubation with 1 μM amphetamine (11). Nevertheless, the region-specific differences in CYAM responses suggest that the soma, in contrast to terminals, is not optimized for vesicular release of DA and CYAM.…”
Section: Discussionmentioning
confidence: 99%
“…This contrasts with the recently developed probe FFN102, which was designed to produce increased fluorescence when released to the extracellular space from acidic synaptic vesicles. 11 These results indicate that only a small portion of the APP+ fluorescence signal originates from the releasable synaptic vesicular pool, while the majority of the APP+ signal is derived from an intracellular mixture of labeled nonexocytotic compartments and cellular structures including mitochondria. Our findings are similar to those obtained with the antihypotensive agent amezinium (4-amino-6-methoxy-1-phenyl-pyridazinium salt) reported by others.…”
Section: ■ Discussionmentioning
confidence: 79%
“…We have previously shown that FFN102-loaded presynaptic terminals in dorsal striatum were completely destained through the action of 40 mM KCl. 11 With APP+, however, we found that KCl only partially destained terminal fields compared to ACSF-treated control ( Figure 7). Analysis was accomplished by measuring mean fluorescence intensity of a field of background-subtracted puncta, before and during KCl treatment, and comparing the results to those obtained with a control imaged without KCl treatment.…”
mentioning
confidence: 77%
See 1 more Smart Citation